The Relationship Between Family Support and Treatment Adherence Among Patients With Tuberculosis - Urnila Afriliani; Mohammad Arifin Noor; Suyanto Suyanto (International Journal Of Health Science, 2026)
Tuberculosis is an infectious disease that requires long-term treatment and high compliance to ensure recovery. Family support is a crucial external factor that can influence patient behavior in completing the treatment regimen. This study aims to determine the relationship between family support and the level of medication adherence in tuberculosis patients at Soepardjo Roestam Regional General Hospital and Welahan 1 Community Health Center. The study used a descriptive analytical design with a cross-sectional approach . Data were collected through a family support questionnaire and the MMAS-8 ( Morisky Medication Adherence Scale ) questionnaire and analyzed using the chi-square test . The results showed that most respondents received good family support and had a high level of medication adherence. The results of the bivariate analysis showed a significant relationship between family support and medication adherence. The conclusion of this study is that optimal family support significantly increases medication adherence in tuberculosis patients, which is very important to prevent therapy failure and drug resistance.